Qualitative and Quantitative Evaluation of Overcurrent Protection in Active Distribution Systems - Brayner Grisales-Soto; Sandra Pérez-Londoño; Juan Mora-Flórez (TecnoLógicas, 2022)
Greenhouse gas emissions are considered a global problem, which is why interest in implementing renewable distributed energy resources (DER) is increasing worldwide. However, despite the contributions to the reduction of fossil primary energy sources, the connection of DERs to power grids often gives rise to new problems in control, operation and protection systems that need to be analyzed and solved. The objective of this paper was to compare a conventional overcurrent protection scheme and several adaptive schemes for active distribution networks (ADN). The proposed methodology consisted of performing an analysis of the adaptive protection approaches for ADN. From this evaluation, the most relevant documents were classified according to the main requirements, contributions, and conclusions. Additionally, some of these proposals were tested with conventional overcurrent protection, using the ATP simulator and Python software. Finally, a quantitative and qualitative analysis of the proposed protection approaches was performed in order to identify limitations to be considered in future research work. The results obtained, when considering different faults and modes of operation of the DNA, showed that the conventional protection coordination approach is highly vulnerable to faults when DERs are connected, mainly due to the change in current magnitudes and direction. The adaptive schemes analyzed have adequate performance, however, several application issues need to be analyzed in the future.